Overexpression of beta 2-microglobulin in transgenic mouse islet beta cells results in defective insulin secretion. - Allison, J (1991)
Overexpression of heavy chains of the class I major histocompatibility complex in islet beta cells of transgenic mice is known to induce nonimmune diabetes. We have now overexpressed the secretory protein beta 2-microglobulin in beta cells. Transgenic mice of one lineage had normal islets. Mice of another lineage did not become overtly diabetic but showed significant depletion of beta-cell insulin. When mice were made homozygous for the transgene locus, they developed diabetes. Introduction of the beta 2-microglobulin chain into class I heavy chain transgenic mice resulted in a significant improvement in their islet morphology and insulin content, and the female mice remained normoglycemic. These results suggest that different transgene molecules overexpressed in beta cells can cause islet dysfunction, though not necessarily overt diabetes, and that this effect is mediated by the level of transgene expression. Evidence is provided to show that beta-cell disruption by transgene overexpression occurs at the level of protein and involves a defect in insulin secretion.